PUBLIC ETHICS PUBLIC ETHICS IN THE CLEAN ENERGY TRANSITION: THE MORAL DILEMMA OF GEOTHERMAL DEVELOPMENT IN FLORES ISLAND: PUBLIC ETHICS IN THE CLEAN ENERGY TRANSITION: THE MORAL DILEMMA OF GEOTHERMAL DEVELOPMENT IN FLORES ISLAND - Rizhard Anselmus Ndolu; Henda Taopan; Noni Banunaek (Yayasan Banu Haji Samsudin, 2025)
The transition toward clean energy in Indonesia presents a complex ethical dilemma, particularly in the context of geothermal energy development on Flores Island. Through the Flores Geothermal Island policy, the government aims to establish Flores as a national laboratory for clean energy. However, behind the narrative of a low-carbon transition lies a deep moral and social tension between the state, corporations, and Indigenous communities. This study employs a qualitative descriptive approach based on document analysis and ethical interpretivism to examine the interrelations among social legitimacy, ecological justice, and public ethics in geothermal energy governance. The analysis reveals the dominance of an economic utilitarian paradigm in national energy policy (40%), emphasizing efficiency and investment, while the values of ecological justice (30%), public ethics and participation (20%), and local spirituality (10%) remain marginalized. This imbalance indicates a deficit of public ethics in the clean energy transition process in Flores. The findings highlight the urgent need to transform energy policy ethics from a technocratic orientation toward a paradigm rooted in social, ecological, and spiritual justice. Therefore, clean energy should not be viewed merely as a technological project but as a moral project that honors both humanity and nature.